UPAYA BIMP-EAGA DALAM MEMBANGUN KONEKTIVITAS ANTAR KAWASAN DI INDONESIA - Tia Nur FajriNingtias; Idjang Tjarsono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This is a political economic studies in international relations which describes about development connectivity between Indonesia with BIMP-EAGA’s region. Development of inter-regional connectivity is one of the main aspects for BIMP-EAGA to increase the value of trade and tourism, this is indicated by the formation of Memorandum of Understanding (MoU) between countries in the land and air transport sector. The development of connectivity through these MoU is expected to bring positive influence on the value of international trade and tourism in Indonesia.This is qualitative research which used descriptive methods, and collecting data from books, journals, official publications and relevant websites. This paper used the structuralist perspective and international economic cooperation theory proposed by Caraiani and Georgescu.The result of this research shows that development connectivity through the MoU in the land and air transport sector of BIMP-EAGA eventually have positive impact on the value of Indonesian trade and tourism with the three other member countries. It is indicated by the table and graph of trade and tourism revenue value in Indonesia in 2007 and 2014 period.Key Words : Inter-regional Connectivity, BIMP-EAGA, Trade, Tourism